Ireneusz Gugulski (1935–1989). Nauczyciel (przyczynek do historii inteligencji w PRL) - Kosiński, Krzysztof (Komunizm: System - Ludzie - Dokumentacja, 2023)
The article presents a biography of Ireneusz Gugulski (1935–1989), an outstanding teacher of Polish studies. The source material consists of stories, memories, documents from school archives, and the Security Service files in the Archive of the Institute of National Remembrance. The first part of the article describes the history of the Gugulski family, Ireneusz Gugulski’s path to the teaching profession, his first steps after moving to Warsaw in 1956, the beginnings of his work at the famous Warsaw secondary school named after Tadeusz Reytan, as well as the process of becoming this school’s legend. In the second part, the author analyses the Polish lessons conducted by Gugulski, their academic and educational meaning. Many of his students remembered them as lessons in intellectual courage, teaching them independent interpretation and treating literature as a space for freedom. It is not a coincidence that some of Gugulski’s students became the leading activists of the so-called democratic opposition in the period of the Polish People’s Republic. The third part of the article deals with the political contexts of Gugulski’s biography: his disciplinary dismissals, involvement in the “Solidarity” movement, internment during the martial law, attempts to return to “his” secondary school, that is the Tadeusz Reytan General Secondary School No. 6. The article also provides information on Gugulski’s private life and introduces the everyday life of an intellectual family under the Polish People’s Republic. Gugulski’s life adds up to several thousand students, among them several dozen professors of literature, teachers, actors, directors, photographers, and doctors. Many of them still consider meeting Gugulski as a turning point. The paper is also a sociological reflection on the formation of the intelligentsia as a social group.